Modified Carroll's pyramid of corporate social responsibility to enhance organizational performance of SMEs industry. (20th October 2020) - Lu, Jintao; Ren, Licheng; Zhang, Chong; Rong, Dan; Ahmed, Rizwan Raheem; Streimikis, Justas
Abstract: Research questions/issues: The study seeks to examine Carrolls' pyramid model in small-medium enterprises (SMEs) as an effective business strategy for organizational performance enhancement in industry of developing country which is in the initial phase of Industry 4.0 advance. The Corporate social responsibility (CSR) pyramid is important tool for fostering environmentally-sustainable manufacturing by having green manufacturing processes, green supply chain management, and green products and holds that firms should engage in relevant decisions, actions, policies and practices that simultaneously fulfill all component parts: ethical, legal, economic, philanthropic and environmental. Research findings/insights: Organizational innovation as a mediator and corporate image as a moderator were incorporated in the modified conceptual model of Carroll's pyramid. 888 valid responses from Small medium enterprises (SMEs) professionals in Pakistan manufacturing sector were collected, and then the structural equation modeling (SEM) based multivariate and conditional process modeling approaches were employed to conduct the investigation. Results demonstrated that the dimensions of modified Carroll's pyramid of CSR have an affirmative and positive impact on the organizational performance of industrial SMEs if they were properly addressed in their innovation strategies. The findings further concluded that organizational innovation and corporate image are the significant mediator and moderator respectively between the dimensions of Carroll's pyramid of CSR and the organizational performance that further enhance the organization performance and productivity in terms of ethical and sustainable business development and overall bottom line in the light of industry 4.0 approach. The outcomes confirmed that the inclusion of Industry 4.0, Cleaner Production, and Circular Economy concepts in the SME sector provides a synergistic business opportunity that intent to payback towards sustainable development by improving environmental management, production efficiency, and socially sustainable development for SMEs. Theoretical/academic implications: This study provides empirical support for the modified Carol's pyramid in industrial SMEs following Industry 4.0 approach. As such, it suggests new avenues of research for both the Industry 4.0 literature, as well as for the studies in CSR and organizational performance perspective. Practitioner/policy implications: Outcomes of this study suggest the senior managers of SME in industrial sector that implementing the modified CSR model would be an innovative and competitive business strategy in industry, which can effectively improve the organizational performance in terms of ethically, ecologically, and economically through organizational innovations and allows to foster Industry 4.0 development.